Biodiversity conservation and armed conflict: a warfare ecology perspective. Issue 1 (23rd April 2018) - Hanson, Thor
Abstract: The activities involved in preparing for, executing, and recovering from armed conflict are globally pervasive and consequential, with significant impacts on natural systems. Effects on biodiversity are predominantly negative, produced by direct and indirect battlefield impacts, as well as the general breakdown of social, economic, and governance systems during wartime. Certain conservation opportunities do occur, however, particularly on lands set aside for training exercises, buffer zones, and peace parks. Here, the relationship between armed conflict and biodiversity is reviewed using the temporal framework of warfare ecology, which defines warfare as an ongoing process of three overlapping stages: preparations, war (armed conflict), and postwar activities. Several themes emerge from recent studies, including a heightened awareness of biodiversity conservation on military lands, the potential for scientific and conservation engagement to mitigate negative biodiversity impacts in war zones, and the importance of the postwar period for incorporating biodiversity priorities into reconstruction and recovery efforts. Research limitations and knowledge gaps are also discussed.